Hydraulic test rig - Healey, M. (College of Aeronautics, 1964)
Hydraulic Test Rig The rig comprises a grinding wheel head spindle driven by a motor and carrying an inertia load made up of detachable steel discs. On the opposite end of• the shaft to the motor is mounted a radial diffraction grating and a d.c. tachogenerator (see Fig. 1). Three motors are currently available, all with there own mounting brackets for easy changing: a) Vickers-Sperry, 6 axial pistons motor type MF-3906-30. b) Boulton Paul; 9 radial pistons with shaped cam track. c) Hartmann Rol-vane H.T.10 (Telehoist). Two types of spool valve are available: a) Dowty Moog, Series 22 b) Pegasus type 120. A manifold block is available to make the two Moog valves interchangeable. The Bolton Paul and Telehoist motors both have double ended shaft so that a tachometer can be mounted direct onto the motor. The tacho used in a Servo tech. (5 rads/sec./volt). The other tacho (mounted on the test rig) is an Evershed-Vignoles (7.9 rads/sec./volt). The Evershed is about 50% less noisy … [cont].